Headache disorders: a persistent public health challenge for the under 50s - Meng, Weijian; Sui, Liutao (Frontiers in Neurology, 2024)
Introduction:Currently,neurological diseases has surpassed cardiovascular diseases as the primary cause of global disease burden. Among these, headache disorders are the most prevalent and have emerged as the main cause of disability in people under 50 years old in recent years.Since the release of GBD 2021, there has been no comprehensive systematic exposition on the burden of headache among individuals under 50 years old and a forecast for future burdens.This study aims to quantify the global, regional, and national burden of headache disorders among people under 50 from 1992 to 2021 and to predict future trends in order to provide policy makers with precise and effective epidemiological evidence. 680 million, 2.33 billion and 41 million, respectively, indicating that the burden of headache disorders in this age group will continue to persist.Conclusions:Globally, the burden of headache disorders in people under 50 years of age remains significant and has not improved over the past 30 years,especially in regions with high SDI.Headache problems will continue to pose a serious public health challenge for this age group for some time to come. This study reveals the burden and distribution of headache disorders in this age group, providing important basis for governments and policymakers to accurately and effectively allocate health care resources, strengthen prevention and management strategies, and respond to this global health problem.